2023
DOI: 10.1186/s12888-023-05009-y
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic changes of intrinsic brain local connectivity in internet gaming disorder

Abstract: Background Studies have revealed that intrinsic neural activity varies over time. However, the temporal variability of brain local connectivity in internet gaming disorder (IGD) remains unknown. The purpose of this study was to explore the alterations of static and dynamic intrinsic brain local connectivity in IGD and whether the changes were associated with clinical characteristics of IGD. Methods Resting-state functional magnetic resonance imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Niu et al. ( 15 ) found a negative correlation between the dReHo value of the left caudate nucleus and the PSQI total score. Our study, however, shows that the FC between the rMFG and bilateral PoCG plays an important role in the sleep quality of male IGD patients, expanding on previous findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Niu et al. ( 15 ) found a negative correlation between the dReHo value of the left caudate nucleus and the PSQI total score. Our study, however, shows that the FC between the rMFG and bilateral PoCG plays an important role in the sleep quality of male IGD patients, expanding on previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…FC links spatial regions of interest via linear time correlation (14). In recent studies, Niu et al (15) applied both static and dynamic ReHo to male IGD individuals and found compromised connectivity within the frontal-striatal-thalamic circuit. Moreover, a longitudinal study of ReHo markers during natural recovery from IGD highlighted the critical involvement of specific brain regions including the dorsolateral prefrontal cortex (DLPFC), orbitofrontal cortex (OFC), and superior frontal gyrus (SFG), which are linked to reward and inhibitory control processes (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation